Applying binary decision diagram to extract concepts and association rules from a triadic contexts [recurso eletrônico]/Júlio César Vale Neves ; orientador: Mark Alan Junho Song - Neves, Júlio César Vale (2021)
Tese (Doutorado) - Pontifícia Universidade Católica de Minas Gerais, Programa de Pós-Graduação em Informática.